Pemberdayaan duta anti narkoba Kota Malang melalui pelatihan dalam upaya peningkatan pengetahuan P4GN - Dimas Setyadi Putra (Altruis: Journal of Community Services, 2022)
Narkoba is an abbreviation of narcotics and drugs/dangerous substances, this term has the same meaning as narcotics, psychotropic substances, and addictive substances (NAPZA) when consumed can affect the human body, especially in the central nervous system can causing disturbances in psychic, physical and social functions due to addiction. Continuous use of drugs outside of medical indications is called abuse. The Anti-Drug Ambassador of Malang City is a forum for those who are elected, who are not only competent but also smart, have good personalities and are attractive. The Anti-Drug Ambassador is a place to find cadres to carry out the task of preventing, eradicating, abusing and illicit narcotics trafficking (P4GN) to the community, which has various work programs and ways to invite people to stay away from drugs. The implementation method was carried out through several stages to determine the knowledge of the Anti-Drug Ambassador of Malang City, starting from the making of the material, the pretest stage, the coaching stage, and the post-test stage. From the results of filling out the questionnaire, the average value of pretest was 75.1 and posttest was 85.4, so it can be concluded that there was an increase in knowledge after being given training.